IMPLEMENTATION OF ANIMAL WELFARE ON PIG FARMS IN SEBATU AND TARO VILLAGE, TEGALLALANG DISTRICT, GIANYAR BALI - Dewi, Ni Putu Juni Ratna; Agustina, Kadek Karang; Mufa, Romy Muhammad Dary (Buletin Veteriner Udayana, 2024)
The increasing demand for pork has led some farmers to allegedly ignore animal welfare principles, focusing more on achieving high production targets. The purpose of this study was to determine the application of animal welfare standards on pig farms in Sebatu and Taro Village, and see the differences between the two villages. The method used was a survey of farmers, namely 25 farmers in each of the two villages. The data obtained were analysed descriptively and comparatively. The results showed that pig farmers in Sebatu and Taro villages have implemented animal welfare very well 54% and 46%. Comparative analysis found no difference in the application of animal welfare between the sampling villages. It can be concluded that the principles of animal welfare have been fulfilled for pigs in Sebatu and Taro Village. It is recommended that farmers reduce the use of battery cages, and provide enrichment facilities for pigs to express their natural habits.